Pengaruh Pembelajaran Blended Learning terhadap Hasil Belajar Siswa pada Pelajaran PAI Kelas VII di SMP PGRI Cicalengka - Indri Ismi Fauziah (Journal of Teacher Training and Educational Research, 2024)
The aim of this research is to find out the influence of Blended Learning on Class VII PAI Lessons at Pgri Cicalengka Regency Middle School. Bandung. This research uses a quantitative approach with descriptive research methods. From the total population there are 138 people, so according to this opinion the number of samples in this study can be taken as 25% of the total population, so that the sample size for this study is 35 people. Based on table 4.29 above, the regression equation that connects variables X with Y is y = -0.100 x + 87.005, which means that Blended Learning has a negative effect on student learning outcomes. This can be seen from the coefficient X = -0.100 which is negative. This means that it can be concluded that the influence of blended learning has nothing to do with student learning outcomes. Keywords: Blended learning, learning outcomes, students